Fiscal Deficits, Asset Prices and Intergenerational Distribution in an Open Unionized Economy. - Erling Steigum (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
This paper focuses on intergenerational welfare effects of fiscal deficits in an OLG model with wage bargaining and equilibrium unemployment. Changes in wage and profit tax rates alter the intergenerational distribution by affecting capital accumulation as well as the price of a fixed asset. The welfare effect on the first old generation crucially depends on the tax instruments applied. The intergenerational welfare effects of postponing labor taxes are qualitatively similar to the effects in a model without unions. Increased union power will depress output and the asset price, but the sign of the welfare effect in steady state is nevertheless ambiguous.
Keywords: 330